Buckling Capacity Of Cold-Formed Steel Structure Column Member With Perforation Section In Affordable House Framing System - Mustafa, Zafira Nur Ezzati (Universiti Sains Malaysia, 2017)
Cold formed C-column have been used in interior wall construction. Because of the issue of material cost become one of the factors need to be considered in affordable house construction, the construction sector has introduced the concept of opening to the column web. Besides, this study focus on the buckling capacity for C-column cold formed steel with perforation. This study starts with determining the suitable spacing for the space column for the affordable house. Analysis house frame has been done in STAAD Pro. analysis using C-column without perforation. Opening with circular shape has been used in this study with the size of 0.4D, 0.6D and 0.8D (D=180mm). Spacing within the opening is 150mm, 250mm and 350mm. for the specimen with 0.4D opening and the edge distance is 539mm have the highest buckling capacity (26.59 kN). Reduction of buckling capacity is 5.31% from C-column without perforation and reduction of volume is -2.16%. for the same case with 0.8D opening, the buckling capacity reduce with 22.52% and volume is -6.85%. the conclusion of this study, C-column without perforation have higher buckling capacity compare to C-column with perforations.